Postharvest physiological responses of pomegranate fruit (cv. Wonderful) to exogenous putrescine treatment and effects on physico-chemical and phytochemical properties - Olaniyi Amos Fawole; Julian Atukuri; Ebrahiema Arendse; Umezuruike Obia Opara (Food Science and Human Wellness)
Pomegranate fruit (cv. Wonderful) were treated with putrescine (1, 2 and 3 mmol/L) before storage for 4 months at 5 °C and 95 % RH and the effects on postharvest life and quality attributes were studied. Results showed that incidence of physiological disorders such as external decay, husk scald, chilling injury and aril browning increased with progressive storage but treating pomegranate fruit with putrescine reduced incidence of most disorders. Control fruit had higher levels of external decay (1.72 %–33.26 %), chilling injury (10.53 %–38.77 %) and scalding (15.04 %–100 %) with less attractive color during 4 month storage. Variations were observed on other fruit quality parameters although treatment with putrescine at 2 and 3 mmol/L concentration reduced changes in color, total soluble solid, Titratable acidity and ascorbic acid. Sensory parameters were best preserved in fruit treated with 2 mmol/L concentration of putrescine with respect to juiciness and crispness. Treatment of pomegranate fruit with putrescine resulted in improved storability and fruit quality during storage. Therefore, for short term storage, 2 mmol/L concentration of putrescine could be recommended for maintaining fruit quality especially in the first two months of storage. However, for longer storage period, a higher concentration is recommended, as 3 mmol/L concentration was the most effective in alleviating disorders and maintaining physico-chemical parameters and sensory attributes during storage in this study.